The Inhibitory Effect of East Indonesia Endemic Plant Itchy Leaves on Staphylococcus epidermidis as a Normal Skin Flora - Malawat, Siti Rabida Nurhasanah; Warella, Juen Carla; Bandjar, Fitri Kadarsih; Effendi, Effendi (Universitas Negeri Surabaya, 2025)
Itchy leaf (Laportea decumana) is one of the plants endemic to Eastern Indonesia. People usually use itchy leaves as an alternative treatment for pain and soreness by rubbing it on the surface of the body. Itchy leaves are very useful because they contain abundant secondary metabolites. The application of itchy leaves by rubbing can certainly affect normal skin flora such as Staphylococcus epidermidis, leading to health problems. This study aimed to investigate the effect of methanol extract of itchy leaves on the normal skin flora of S. epidermidis. This test was conducted using the disk diffusion method. The results of this study showed that all concentrations of itchy leaf extract inhibited the growth of S. epidermidis. The highest inhibitory activity was observed at 50% concentration (23.00 ± 7.20), categorized as very strong, followed by 100% concentration (15.00 ± 2.90), 25% (18.00 ± 11.3), 12.5 (13.40 ± 3.51), and 6.25 (10.40 ± 3.10), all categorized as strong. These findings indicate that the prolonged use of itchy leaves may affect the growth of normal flora, resulting in health problems. On the other hand, itchy leaves have the potential to be developed as an antibacterial agent in the future.